DOMINASI MILITER DALAM POLITIK DAN PEMERINTAHAN DI MESIR: KEGAGALAN DEMOKRATISASI DI MESIR PADA KUDETA 2013 - Afini Nurdina Utami; Syaiful Anam (Review of International Relations, 2022)
This paper discusses how the democratization process that took place for the first time in Egypt, which was marked by the election of President Mohammad Morsi and the victory of Islamic groups' votes in parliament through this general election, did not run smoothly. The military, which has long been in an important position in Egypt, is not standing still. The democratic process in Egypt was marred by the coup carried out by the military group against the Morsi government on July 3, 2013. Through an analysis based on pretorian theory and the concept of military intervention in politics, this paper shows the dominance of the military as a very dominant actor in Egypt. Pretorian theory, in particular, emphasizes the dominant role of the military in all important political institutions, including political leaders. The military, which was previously allied with the Muslim Brotherhood and supported the Egyptian revolution that resulted in the ouster of President Mubarak, turned into opponents when IM won a majority in the Egyptian parliamentary elections. The military saw that the voice of Islamic groups was no longer in line with its interests, so the 2013 coup against Muhammad Morsi took place.